2013
DOI: 10.1007/s00415-013-6996-x
|View full text |Cite
|
Sign up to set email alerts
|

Handwriting as an objective tool for Parkinson’s disease diagnosis

Abstract: To date, clinical assessment remains the gold standard in the diagnosis of Parkinson's disease (PD). We sought to identify simple characteristics of handwriting which could accurately differentiate PD patients from healthy controls. Twenty PD patients and 20 matched controls wrote their name and copied an address on a paper affixed to a digitizer. Mean pressure and mean velocity was measured for the entire task and the spatial and temporal characteristics were measured for each stroke. Results of the MANOVAs f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
103
1
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(122 citation statements)
references
References 23 publications
8
103
1
6
Order By: Relevance
“…The results are in accordance with previous studies [6,9,11,13]. However, former studies have merely compared handwriting of PD patients and healthy controls and have not looked into different types of paper as possible cues for improving handwriting.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results are in accordance with previous studies [6,9,11,13]. However, former studies have merely compared handwriting of PD patients and healthy controls and have not looked into different types of paper as possible cues for improving handwriting.…”
Section: Discussionsupporting
confidence: 91%
“…According to previous studies [6,8,13] the handwriting speed of people with PD is slower compared to age-and gender-matched healthy individuals and. Changes in handwriting occur prior PD is diagnosed, being one of the first symptoms of the illness [11].…”
Section: Introductionmentioning
confidence: 99%
“…If we consider dysgraphia in PD from this point of view, we reach the following conclusions: handwriting impairment was found to be positively correlated with an accurate diagnosis of PD [17,18]; correlations between handwriting variables and clinical evaluations in PD patients (motor part of the Unified Parkinson's Disease Rating Scale [19]) were found in several studies (e.g., [9,12]); changes in handwriting increase with PD progression [7]; there is still a need to confirm the preclinical status of handwriting impairment; many studies led by experts have specifically targeted an understanding of handwriting impairment in PD (for a review, see [14,20]). In addition, it has been reported that short and routine writing tasks based on kinematics analyses could help to distinguish PD patients from controls [7].…”
Section: From Micrographia To Dysgraphia In Parkinson's Diseasementioning
confidence: 86%
“…Consequently, as part of the identification of new and objective biomarkers to help diagnose PD at its earliest stage and manage disease progression, handwriting analysis has been proposed [5][6][7]. Until recently, there was a consensus regarding the existence of a specific behavioral feature in PD handwriting, so-called micrographia.…”
Section: Micrographia In Parkinson's Disease: Too Restrictive a Definmentioning
confidence: 99%
See 1 more Smart Citation